Teachers' Perspectives towards Validity of Teacher-Made Test - Hasnan Yasin; Septia Tri Gunawan; Nida Husna; Didin Nuruddin Hidayat (Edukasi, 2020)
Some studies that had been conducted showed that teacher-made tests were good and satisfactory. However, the majority of teachers do not validate their tests administering them to the students. This study would describe the perspective of teachers towards their-own.-made (teacher-made) tests they have made to know that to what extent their agreement regarding their attitudes, quality, and use of the tests. Five English teachers participated in this research. Their view on the test they have made would be analyzed and described. The results showed that (1) the teachers agreed about the appropriateness of the test they administered; (2) the teachers believed that the data quality obtained during research was useful and meaningful, and; (3) the teachers used the test to identify and to evaluate their learning objectives, students’ learning needs, students’ learning difficulties, and school evaluation.